Effectiveness of Chewing Pineapple (Ananas Comosus L. Merr) Against Debris Index in Class V Students of SDN Barengkrajan 1 Sidoarjo 2024 - Arnita Dwi Meilani; Sri Hidayati; Silvia Prasetyowati; I Gusti Ayu Kusuma Astuti N (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Pineapple is a fruit that is popular with many people because its taste is generally sweet and slightly sour, the aroma is very fragrant and it is easy to find everywhere. Pineapples contain quite a lot of fiber and water and contain active substances such as the enzyme bromelain and flavonoids which function as antibacterials so they can stop the growth of plaque bacteria and reduce the growth of Streptococcus mutans bacteria. Then pineapple contains citric acid which can increase saliva secretion and pineapple contains iodine and phenol which functions as an antiseptic. The aim of this research was to determine the effectiveness of chewing pineapple on the debris index in class V students at SDN Barengkrajan 1 Sidoarjo. The method in this research was carried out by collecting index debris data for class V students at SDN Barengkrajan 1 Sidoarjo, totaling 30 students, using an index debris examination sheet by carrying out direct observations of respondents and providing intervention in the form of chewing pineapple. Data analysis using the Wilcoxon test. The results showed that there was a decrease in the debris index in class V students at SDN Barengkrajan 1 Sidoarjo between before and after being given the intervention, namely from bad to moderate. There is the effectiveness of chewing pineapple on the debris index in class V students at SDN Barengkrajan 1 Sidoarjo.